Peningkatan Kesejahteraan Petani melalui Penerapan Teknologi Pertanian Berbasis Smart Farming di Desa Durian Kecamatan Janapria - Fajri, Muliadi (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to analyze the implementation of smart farming-based agricultural technology in improving the welfare of farmers in Durian Village, Janapria District. Smart farming is a modern agricultural approach that utilizes information and communication technology (ICT) to enhance production efficiency, resource management, and data-driven decision-making. The research employs a descriptive method with a qualitative approach. Data were collected through in-depth interviews, field observations, and document studies. The findings reveal that the implementation of technologies such as soil sensors, automated irrigation, drone-based land monitoring, and mobile applications for farm management significantly increased land productivity by 25%. Additionally, farmers' incomes rose by an average of 20% annually due to more efficient management and reduced production costs. However, challenges include farmers' limited technological understanding, inadequate infrastructure, and relatively high initial costs. This study recommends strengthening training programs for farmers, developing supporting infrastructure, and providing government subsidies to expand the adoption of smart farming technology. Thus, the application of smart farming demonstrates significant potential to enhance the welfare of rural farmers.